Hubungan kinerja otak dan spiritualitas manusia diukur dengan Indonesia Spiritual Health Assessment pada tokoh agama Islam di Kabupaten Bolaang Mongondow - Pakaya, Putra; Pasiak, Taufiq F.; Kalangi, Sonny J.R. (e-Biomedik, 2017)
Abstract: Human brain contains about 100 billion cells that have complex functions as the central control of all activities. The brain is an organ in which the interaction of soul and body (mind body interaction) occurs and is very influential on human spirituality. Spirituality is built by four observable aspects, as follows: spiritual experience, positive emotion, meaning of life, and ritual. Health Law of the Republic of Indonesia Number 36 Year 2009 Chapter I Article 1 Paragraph 1 defines health by integrating the spiritual aspect as part of the definition of health. Indonesia Spiritual Health Assessment (ISHA) is a neuroscience-based test that includes human spirituality profile so it can find spirituality and its relation to brain performance. This study was aimed to determine the relationship of brain performance and human spirituality among Islamic religious leaders in Bolaang Mongondow. This was an observational study with a cross sectional design. There were 57 Islamic religious leaders as respondents. Data were retrieved by distributing questionnaires ISHA to the respondents. The statistical analysis showed that the correlation between temporal lobes and spiritual experience had an r value = 0.304 and p value = 0.022. Conclusion: There was a relationship between the performance of the brain and human spirituality in particular the relationship between the temporal lobe and spiritual experience among Islamic religious leaders in Bolaang MongondowKeywords: brain performance, spirituality Abstrak: Otak manusia berisi sekitar 100 miliar sel yang memiliki fungsi kompleks sebagai pusat pengendali seluruh aktivitas manusia. Otak merupakan organ tubuh dimana terjadinya interaksi ‘jiwa’ dan ‘badan’ (mind body interaction) yang sangat berpengaruh terhadap spiritualitas manusia. Spiritualitas dibangun oleh empat aspek yang dapat diamati yaitu pengalaman spiritual, emosi positif, makna hidup, dan ritual. Undang-Undang Kesehatan Republik Indonesia Nomor 36 Tahun 2009 Bab I Pasal 1 ayat 1mendefinisikan kesehatan, yaitu dengan memasukkan aspek spiritual sebagai bagian dari batasan sehat. Indonesia Spiritual Health Assessment (ISHA) merupakan uji berbasis neurosains yang memuat tentang profil spiritualitas manusia sehingga dapat mengetahui spiritualitas dan kaitannya dengan kinerja otak. Penelitian ini bertujuan untuk mengetahui hubungan kinerja otak dengan spiritualitas manusia pada tokoh agama Islam di Kabupaten Bolaang Mongondow. Jenis penelitian ialah observasional dengan desain potong lintang. Terdapat 57 orang tokoh agama Islam di Kabupaten Bolaang Mongondow sebagai responden. Data diambil dengan cara membagikan kuisioner ISHA kepada responden. Hasil analisis statistik menunjukkan korelasi antara lobus temporalis dengan pengalaman spiritual (r=0,304; p=0,022). Simpulan: Pada tokoh agama Islam di Kabupaten Bolaang Mongondow terdapat hubungan antara kinerja otak dengan spiritualitas manusia khususnya hubungan one to one antara lobus temporalis dan pengalaman spiritual.Kata kunci: kinerja otak, spiritualitas